2016
DOI: 10.3847/0004-637x/826/2/114
|View full text |Cite
|
Sign up to set email alerts
|

A SYSTEMATIC SURVEY OF PROTOCLUSTERS AT z ∼ 3–6 IN THE CFHTLS DEEP FIELDS

Abstract: We present the discovery of three protoclusters at z ∼ 3-4 with spectroscopic confirmation in the Canada-FranceHawaii Telescope Legacy Survey Deep Fields. In these fields, we investigate the large-scale projected sky distribution of z ∼ 3-6 Lyman-break galaxies and identify 21 protocluster candidates from regions that are overdense at more than 4σ overdensity significance. Based on cosmological simulations, it is expected that more than 76% of these candidates will evolve into a galaxy cluster of at least a ha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
137
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 96 publications
(144 citation statements)
references
References 86 publications
(138 reference statements)
6
137
1
Order By: Relevance
“…Object detection and LBG sample selection were performed in the same manner as Toshikawa et al (2016). In this section, we present a brief outline of the photometry and the sample selection method.…”
Section: Photometry and Sample Selectionmentioning
confidence: 99%
“…Object detection and LBG sample selection were performed in the same manner as Toshikawa et al (2016). In this section, we present a brief outline of the photometry and the sample selection method.…”
Section: Photometry and Sample Selectionmentioning
confidence: 99%
“…Although there is a large scatter due to projection effects, surface overdensity significance is closely correlated with descendant halo mass at z = 0. Toshikawa et al (2016) showed that > 76% of > 4σ overdense regions of g-dropouts are expected to evolve into dark matter halos with masses of > 10 14 M⊙at z = 0 although there is no clear difference between < 4σ overdense regions and fields due to a large scatter. It should be noted that the success rate of this technique has already been established by our previous study of the ∼4 deg 2 of the CFHTLS Deep Fields, as the precursor of this HSC protocluster search, followed by Keck/DEIMOS and Subaru/FOCAS spectroscopy (Toshikawa et al 2016).…”
Section: Hsc Protocluster Samplementioning
confidence: 99%
“…The expected 5σ limiting magnitudes for point sources are (g, r, i, z, y) = (26.5, 26.1, 25.9, 25.1, 24.4) mag measured in 2.0 arcsec apertures. We expect to obtain > 1400 protocluster candidates at z ∼ 4 by the end of the survey (Toshikawa et al 2017(Toshikawa et al , 2016. The HSC data (DR S16A Aihara et al 2017), which includes data taken before April 2016, has already produced an extremely wide field image of > 200 deg 2 with a median seeing of 0.…”
Section: The Subaru Hsc-ssp Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…We also check the spectroscopic catalogs shown in other studies (Saito et al 2008;Ouchi et al 2008;Willott et al 2010a;Curtis-Lake et al 2012;Masters et al 2012;Mallery et al 2012;Willott et al 2013;Le Fèvre et al 2013;Kashikawa et al 2015;Kriek et al 2015 4 ; Wang et al 2016;Toshikawa et al 2016;Momcheva et al 2016;Matsuoka et al 2016;Pâris et al 2017;Tasca et al 2017;Yang et al 2017;Masters et al 2017;Matsuoka et al 2017;Shibuya et al 2017b; R. Higuchi et al in preparation; see also Bañados et al 2016 whose redshifts are > 70 − 75% correct, i.e., sources with redshift reliability flags of 2, 3, 4, 9, 12, 13, 14, and 19. Here we focus on sources with spectroscopic redshifts zspec > 3 in these catalogs.…”
Section: Source Selectionmentioning
confidence: 99%